Dual isotope stress testing in congenital atresia of left coronary ostium. Applications before and after surgical treatment. Issue 3 (March 1980) - Dymond, D; Camm, J; Stone, D; Rees, S; Rees, G; Spurrell, R
Abstract : A 38-year-old women presented with an 11-year history of angina pectoris. Coronary arteriography disclosed a large right coronary artery which filled the entire left coronary tree retrogradely. The left main coronary artery ended blindly and was not connected to the aortic root. There were no atherosclerotic lesions in any vessel. Exercise thallium-20l scintigrams showed a perfusion defect in the anterior region of the left ventricle and exercise first pass radionuclide ventriculography showed anterior hypokinesis of the left ventricle with an ejection fraction of 54 per cent, compared with 60 per cent at rest. An aortocoronary saphenous vein graft was constructed to the left coronary artery. Four months after operation the patient is free from symptoms. Repeat thallium scintigrams were normal. Exercise radionuclide ventriculography after operation disclosed no wall motion abnormality, and ejection fraction on exercise was 70 per cent. The mechanism of angina in this patient is unclear but may have been related to the abnormal timing of delivery of blood to the left ventricular myocardium. Dual radionuclide stress testing showed abnormalities after operation. This non-invasive approach may be useful in the assessment of the physiological significance of coronary anomalies and of the value of corrective surgery.